DESAIN PRIMER SECARA IN SILICO UNTUK AMPLIFIKASI GEN tcdA BAKTERI CLOSTRIDIUM DEFFILCILE - Dewi , I Gusti Agung Ayu Satwikha; Octifani , Amellya (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Antibiotics are drugs used to fight infections caused by bacteria. C. difficile bacteria is a bacterium that causes Clostridium difficile infection (ICD). Toxin A of C. difficile bacteria is exotoxin A (tcdA) which is a virulence factor that causes disease. Toxin A can damage the intestinal mucosa and cause bleeding. The cost of examining and treating patients with AAD and PMC is very high, so the dosage must be determined correctly. Laboratory tests function to determine the presence or absence of an ICD. The discovery of specific biomarkers is a discovery priority to improve the quality of laboratory tests. Specific primary design is an important step in all types of laboratory examination methods, one of which is molecular examination by PCR. The primary design must have specific properties so as to be efficient at target amplification. This study aims to obtain a primer design that can be used to limit the amplification area of the TcdA gene in silico. This study used a literature study from the NCBI genbank to obtain the tcdA gene sequence of C. defficile bacteria with accession number DQ902560.1. The tcdA gene sequence of C. difficile bacteria was analyzed using Primer3Plus to determine whether there is hairpin and dimer formation. Furthermore, identification was carried out using web-based in silico PCR to determine the number of amplicon and visualization on the electrophoretic gel. The level of tcdA gene homology in the species group in the BLAST test. The results showed that the best primer design for in silico detection of the tcdA gene of C. difficile was the forward primer 5'-GCAGATGCCAAGAGACACAC-3' and the reverse primer 3'-GCAGATGCCAAGACACACAC-5'. The primary design is able to amplify the tcdA gene region with a size of 247 amplicons.